Board structure and price informativeness☆ - Ferreira, Daniel; Ferreira, Miguel A.; Raposo, Clara C. (Journal of Financial Economics, 2011)
We develop and test the hypothesis that stock price informativeness affects the structure of corporate boards. We find a negative relation between price informativeness and board independence. This finding is robust to the inclusion of many firm-level controls, including firm fixed effects, and to the choice of the measure of price informativeness. Consistent with the hypothesis that price informativeness and board monitoring are substitutes, this relation is particularly strong for firms more exposed to both external and internal governance mechanisms and for firms in which firm-specific knowledge is relatively unimportant. Our results suggest that firms with more informative stock prices have less demanding board structures.